Healthcare access among circular and undocumented Mexican migrants: results from a pilot survey on the Mexico-US border. (1st January 2014) - Martínez-Donate, Ana P.; Zhang, Xiao; Rangel Gomez, M. Gudelia; Hovell, Melbourne F.; Simon, Norma-Jean; Amuedo-Dorantes, Catalina; Sipan, Carol; Guendelman, Sylvia
Temporary and unauthorised migrants may face unique obstacles to access healthcare services in the USA. This study estimated levels of healthcare access among Mexican migrants returning to Mexico from the USA and factors associated with access to healthcare, with emphasis on the role of modifiable, enabling factors. We conducted a pilot probability healthcare survey of migrants in the border city of Tijuana, Mexico (N = 186). Approximately 42% of migrants reported having used healthcare services in the USA during the past year. Only 38% had a usual source of care and approximately 11% went without needed medical care in the USA. About 71% of migrants did not have health insurance in the USA. Lack of health insurance and transportation limitations were significantly related to various access indicators. These results have implications for future policies and programmes aimed to address modifiable healthcare access barriers faced by these vulnerable and underserved segments of the Mexican migrant population.